Global key concepts of civil-military cooperation for disaster management in the COVID-19 pandemic: a qualitative phenomenological scoping review - Ries, Markus (Research Square, 2022)
Background: In the context of a holistic and comprehensive disaster response effort to the COVID-19 pandemic, many countries across the globe mobilized their military forces in order to cope with sudden and exponential surges of critically ill patients with COVID-19 in stretched healthcare sys...